“Privacy Is Overrated”: Situating the Privacy-related Beliefs and Practices of Italian Parents with Young Children - Zaffaroni, Lorenzo Giuseppe (Surveillance & Society, 2024)
The widespread surveillance of everyday family life poses threats to parents’ and children’s right to privacy. Even though considerable research on privacy in families with young children exists, more evidence on the interplay between contextual factors and privacy issues is needed to enrich our understanding of privacy as grounded in everyday family life. To this aim, this paper conceptualises privacy as a situated and emergent phenomenon related to family cultures, socioeconomic background, technological imaginaries, and other significant markers of everyday family life. Drawing on qualitative data from a longitudinal research project with parents of children aged zero to eight, the study shows that privacy risks and threats are mostly associated with the interpersonal context; corporate and institutional surveillance are naturalised within notions of convenience or resignation to big-tech corporations. As technological and surveillance imaginaries influence such a complex web of privacy dynamics, this paper advocates for a situated and contextual approach to family privacy and surveillance in times of datafication.